2007
DOI: 10.1099/jmm.0.47330-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing divides marine mammal strains of Brucella into at least three groups with distinct host preferences

Abstract: In order to investigate the genetic relationships within Brucella isolated from marine mammals, two genome-based typing methods, variable number of tandem repeats (VNTR) typing and multilocus sequence analysis (MLSA), were applied to a selection of 74 marine mammal isolates. All isolates were examined by VNTR and data were compared with multilocus sequencing data from a subset of 48 of these. Marine mammal brucellae are distinct from classically recognized species by these methods and appear to correspond to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 25 publications
5
68
0
Order By: Relevance
“…When comparing profi les at 6 loci with a relatively slow evolutionary speed, previously shown to be useful for dividing Brucella isolates into species groups (8), we determined that F5/99 and the 3 naturally acquired human isolates share a unique profi le not seen in any of >1,400 isolates of marine or terrestrial Brucella species examined to date. In contrast, the strain associated with laboratory-acquired infection (4) was not a member of ST27 but belonged to ST23, a genotype that is predominantly associated with porpoises (9).…”
mentioning
confidence: 94%
“…When comparing profi les at 6 loci with a relatively slow evolutionary speed, previously shown to be useful for dividing Brucella isolates into species groups (8), we determined that F5/99 and the 3 naturally acquired human isolates share a unique profi le not seen in any of >1,400 isolates of marine or terrestrial Brucella species examined to date. In contrast, the strain associated with laboratory-acquired infection (4) was not a member of ST27 but belonged to ST23, a genotype that is predominantly associated with porpoises (9).…”
mentioning
confidence: 94%
“…11 Other genetic studies support 3 distinct lineages with associated host preferences for pinnipeds, dolphins, and porpoises, although host specificity is not absolute. 13 Information about exposure and disease prevalence in potentially vulnerable marine mammal populations is growing; however, many questions have yet to be answered, including the specifics of transmission, pathogenicity, and susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators reported that MLVA could classify Brucella isolates in accordance with different host origin (Groussaud et al, 2007), geographic region (Kattar et al, 2008), and species (Whatmore et al, 2006). In clustering and traceback analysis, B. abortus isolates from wild animals were included in the same group as isolates from livestock, suggesting that direct or indirect horizontal transfer may occur and that brucellosis in wildlife reservoirs may pose a threat to humans and domestic animals.…”
mentioning
confidence: 97%
“…The MLVA typing assay has been recommended by many researchers to analyze the genetic diversity and to trace the origins of infection (Whatmore et al, 2006;Al Dahouk et al, 2007;Groussaud et al, 2007;Her et al, 2009;Kang et al, 2009;Abril et al, 2011). Seventeen markers (16 loci and HOOF-3) used previously were available for follow-up (Bricker et al, 2003;Her et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation